Structural-functional peculiarities of Equisetum arvense L. rhizomes in ontogenesis - Babenko, L.M.; Shcherbatiuk, M.M.; Kosakivskа I.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The nature of changes in the lipoxygenase activity and the tissue ultrastructure of rootstock horsetail (Equisetum arvense L.) during the physiological rest and during the way out of it are investigated. It is found that going out the dormancy occurs against a background of the increased activity of lipoxygenase. Specific changes that took place in the cell ultrastructure horsetail rhizome, while leaving the rest, are identified. They include reducing the number of starch grains in amyloplast and increasing the number of lipid droplets that form the lipid layer located next to the plasmolemma.